Genetic Variation in Coat Colour Genes MC1R and ASIP Provides Insights Into Domestication and Management of South American Camelids - Marín, Juan C.; Rivera, Romina; Varas, Valeria; Cortés, Jorge; Agapito, Ana; Chero, Ana; Chávez, Alexandra; Johnson, Warren E.; Orozco-terWengel, Pablo (Frontiers in Genetics, 2018)
The domestication of wild vicuña and guanaco by early pre-Inca cultures is an iconic example of wildlife management and domestication in the Americas. Although domestic llamas and alpacas were clearly selected for key, yet distinct, phenotypic traits, the relative patterns and direction of selection and domestication have not been confirmed using genetic approaches. However, the detailed archaeological records from the region suggest that domestication was a process carried out under significant control and planning, which would have facilitated coordinated and thus extremely effective selective pressure to achieve and maintain desired phenotypic traits. Here we link patterns of sequence variation in two well-characterized genes coding for colour variation in vertebrates and interpret the results in the context of domestication in guanacos and vicuñas. We hypothesize that colour variation in wild populations of guanacos and vicunas were strongly selected against. In contrast, variation in coat colour variation in alpaca was strongly selected for and became rapidly fixed in alpacas. In contrast, coat colour variants in llamas were of less economic value, and thus were under less selective pressure. We report for the first time the full sequence of MC1R and 3 exons of ASIP in 171 wild specimens from throughout their distribution and which represented a range of commonly observed colour patterns. We found a significant difference in the number of non-synonymous substitutions, but not synonymous substitutions among wild and domestics species. The genetic variation in MC1R and ASIP did not differentiate alpaca from llama due to the high degree of reciprocal introgression, but the combination of 11 substitutions are sufficient to distinguish domestic from wild animals. Although there is gene flow among domestic and wild species, most of the non-synonymous variation in MC1R and ASIP was not observed in wild species, presumably because these substitutions and the associated colour phenotypes are not effectively transmitted back into wild populations. Therefore, this set of substitutions unequivocally differentiates wild from domestic animals, which will have important practical application in forensic cases involving the poaching of wild vicuñas and guanacos. These markers will also assist in identifying and studying archaeological remains pre- and post-domestication.